Amino Acid Polymorphisms in the VHIID Conserved Motif of Nodulation Signaling Pathways 2 Distinctly Modulate Symbiotic Signaling and Nodule Morphogenesis in Medicago truncatula - Kovacs, Szilárd; Fodor, Lili; Domonkos, Agota; Ayaydin, Ferhan; Laczi, Krisztián; Rákhely, Gábor; Kalo, Péter (Frontiers in Plant Science, 2021)
Legumes establish an endosymbiotic association with nitrogen-fixing soil bacteria. Following the mutual recognition of the symbiotic partner, the infection process is controlled by the induction of the signaling pathway and subsequent activation of symbiosis-related host genes. One of the protein complexes regulating nitrogen-fixing root nodule symbiosis is formed by GRAS domain regulatory proteins Nodulation Signaling Pathways 1 and 2 (NSP1 and NSP2) that control the expression of several early nodulation genes. Here, we report on a novel point mutant allele (nsp2-6) affecting the function of the NSP2 gene and compared the mutant with the formerly identified nsp2-3 mutant. Both mutants carry a single amino acid substitution in the VHIID motif of the NSP2 protein. We found that the two mutant alleles show dissimilar root hair response to bacterial infection. Although the nsp2-3 mutant developed aberrant infection threads, rhizobia were able to colonize nodule cells in this mutant. The encoded NSP2 proteins of the nsp2-3 and the novel nsp2 mutants interact with NSP1 diversely and, as a consequence, the activation of early nodulin genes and nodule organogenesis are arrested in the new nsp2 allele. The novel mutant with amino acid substitution D244H in NSP2 shows similar defects in symbiotic responses as a formerly identified nsp2-2 mutant carrying a deletion in the NSP2 gene. Additionally, we found that rhizobial strains induce delayed nodule formation on the roots of the ns2-3 weak allele. Our study highlights the importance of a conserved Asp residue in the VHIID motif of NSP2 that is required for the formation of a functional NSP1-NSP2 signaling module. Furthermore, our results imply the involvement of NSP2 during differentiation of symbiotic nodule cells.